Universal access to no-cost contraception for youth in Canada - Di Meglio, Giuseppina (Paediatr Child Health, 2019)
Timely access to effective contraception reduces the incidence of unintended pregnancy. Cost is a significant barrier to using contraception for youth in Canada. Many must pay out-of-pocket because they have no pharmaceutical insurance, their insurance does not cover the contraceptives they desire, or they wish to obtain contraceptives without their parents’ knowledge. To address these barriers and reduce rates of unintended pregnancy, this statement recommends that all youth should have confidential access to contraception, at no cost, until the age of 25. The statement also recommends measures to help achieve this goal across Canada.